PROGRAM LITERASI SDN KOTA PEKANBARU, BUKIT LEMBAH SUBUR DAN MANDAU - Rahma, Aisya; Syafira, Ananda Mai; Nurhija, Andan Ela; Al Faseh, Anisa Belly; Dafit, Febrina (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Low Interest in Reading: Students have low interest in reading or are less exposed to a reading culture. Lack of adequate access to interesting and varied reading materials and low reading comprehension. This study aims to evaluate the literacy program implemented in SDN Kota Pekanbaru, Bukit Lembah Subur, and Mandau. The research method used is a qualitative approach using observation techniques and structured interviews with students, teachers and parents. The results showed that the literacy program in the three schools was effective in increasing students' interest in reading, reading skills, and reading comprehension. Supporting factors such as active teacher involvement, parental support, and the use of innovative learning methods also play an important role in the success of literacy programs. However, challenges such as limited resources and lack of time allocated for literacy activities still need attention. Therefore, there is a need for continuous efforts to develop and strengthen literacy programs in these schools in order to improve students' literacy skills